Social Benefit System During the Government Omar ibn Khattab - Eka Hardana, Nugraha; Kholiq, Achmad (Ann Publisher, 2023)
Human behavior is altered by the progress of civilization. It includes elements from the fields of language, art, science, and religion. In the course of this process, civilization develops gradually over a long period of time. During the rule of Caliph Umar Ibn Khattab, one of the greatest civilizations, particularly in the post-Prophet Muhammad era, took place. Utilizing a qualitative descriptive methodology, this study collected data through a literature review. The welfare system under Umar Ibn Khattab's administration is examined in the paper. The results of the literature review show that Umar Ibn Khattab continued the policies started by Abu Bakr and made adjustments to meet the demands of society during his rule as caliph. During Umar Ibn Khattab's leadership, ghanimah (war spoils), usyur (customs duty), kharaj (land tax), jizyah (poll tax), zakat (alms), and other irregular earnings were used to increase social welfare. All of these sources of income were controlled by the Baitulmal system (public treasury). Based on each person's job and the requirements of the community, Umar dispersed social benefits. In order to build a strong human resource base for Islam, Caliph Umar made social investments to safeguard the welfare of children as well. This was done by helping infants until they were old enough to take care of themselves.